Towards a General Framework for an Observation and Knowledge based Model of Occupant Behaviour in Office Buildings. (November 2015) - Tijani, Khadija; Ngo, Quoc Dung; Ploix, Stephane; Haas, Benjamin; Dugdale, Julie
Abstract: This paper proposes a new general approach based on Bayesian networks to model the human behaviour. This approach represents human behaviour with probabilistic cause-effect relations based not only on previous works, but also with conditional probabilities coming either from expert knowledge or deduced from observations. The approach has been used in the co- simulation of building physics and human behaviour in order to assess the CO2 concentration in an office.